Stool Saponified Fatty Acid, Behavior, Growth, and Stool Characteristics in Infants Fed a High-OPO Formula: A Randomized, Double-Blind Clinical Trial - Shen, Lili; Huang, Weihua; Xu, Xuebing; Wang, Li; Wang, Qingyun; Li, Shengqi; Yuan, Xuewei (Frontiers in Pediatrics, 2021)
Objective: 1,3-Dioleoyl-2-palmitoylglycerol (OPO) is an ideal structured triglyceride for infant formula, with a similar structure to human milk fat. We conducted this randomized, double-blind controlled, single-center trial to evaluate the effects of an OPO formula in infants. Study Design: One hundred seventy-four healthy term infants less than 14 days old were assigned to the standard formula-fed group (n=55), high sn-2 palmitic acid (OPO) formula-fed infants (n=58), and breastfed (BF) group (n=61). The primary endpoint was the total saponified fatty acid content in feces at week 6 and week 12. Results: Infants from the OPO group had lower concentrations of fecal saponified fatty acids than those from the standard formula group (p<0.0001) at week 6 and week 12. The frequencies of crying per day and per night of infants in the OPO group were significantly less than those of infants in the standard formula group (p<0.0001). After 12 weeks of feeding, the length of infants was significantly higher in the OPO group than in the other two groups (p=0.002). Infants in the OPO group had a significantly lower stool calcium concentration and a higher stool frequency per day than infants in the standard formula group. Conclusion: In summary, a high concentration of OPO in formula is beneficial to the growth and development of infants.